2018
DOI: 10.3390/su10093096
|View full text |Cite
|
Sign up to set email alerts
|

Industrial or Traditional Bamboo Construction? Comparative Life Cycle Assessment (LCA) of Bamboo-Based Buildings

Abstract: The past five decades have witnessed an unprecedented growth in population. This has led to an ever-growing housing demand. It has been proposed that the use of bio-based materials, and specifically bamboo, can help alleviate the housing demand in a sustainable manner. The present paper aims to assess the environmental impact caused by using four different construction materials (bamboo, brick, concrete hollow block, and engineered bamboo) in buildings. A comparative life cycle assessment (LCA) was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 39 publications
0
48
0
2
Order By: Relevance
“…Life cycle assessment studies of bamboo-based construction materials clearly showed the potential of bamboo for use in the construction sector [7][8][9][10]. In these studies, transportation is an important issue to a product such as bamboo culm which has a high volume per mass.…”
Section: Introductionmentioning
confidence: 99%
“…Life cycle assessment studies of bamboo-based construction materials clearly showed the potential of bamboo for use in the construction sector [7][8][9][10]. In these studies, transportation is an important issue to a product such as bamboo culm which has a high volume per mass.…”
Section: Introductionmentioning
confidence: 99%
“…Instead our goal is to offer an understanding of the comparative environmental impacts of bamboo versus steel in future designs. Here it is also important to mention that our comparative study does not define the functional units in the way that a Life Cycle Assessment (LCA) might do, given that that LCA is expensive and requires great experience and exhaustive detail, yet is still subject to great uncertainty [16]. Our comparison will rather present a reliable insight into the environmental impacts of bamboo versus steel, as based on a range of inventories:…”
Section: Comparative Study Between Bamboo and Steel Constructionmentioning
confidence: 99%
“…Due to the toughness and tensile strength of bamboo, fine strips can be easily curved and woven into mats with different patterns in the same way as fabrics [29,30]. In terms of the raw material itself, the ecology potentials of bamboo as an environmentally friendly resource have been an increasingly considered option in the field of renewable building materials [31][32][33]. Bamboo is widely planted and utilized as industrial or building material in Southern and Southeast Asia [34].…”
Section: Introductionmentioning
confidence: 99%